Ukraine’s External Independent Testing Innovation - Klein, Eduard (International Higher Education, 2014)
In 2008 Ukraine reformed its university admission system and effectively reduced corruption. Despite high confidence ratings, the reform has been watered down since the political change in 2010 and its future remains unclear.